Caspase 3 and Caspase 10 Expression in Rat Muscles Post Gagatan Harimau (Paraboea leuserensis B.L.Burtt) Nanoherbal and Exercise - Ashfira; Syafruddin Ilyas; Masitta Tanjung (Postgraduate, University of Mataram, 2024)
This study aims to analyze the Expression of Caspase 3 and Caspase 10 in Rat Muscles Post Gagatan Harimau (Paraboea leuserensis B.L.Burtt) Nanoherbal and Exercise. Treatment consists of control group, maximum physical exercise, maximum physical exercise + Vitamin C at a dose of 2 mg/Kg Body Weight, maximum physical exercise + Gagatan Harimau nanoherbal with concentration 100, 125 and 150 mg/Kg BW. Data obtained from each observation parameter were recorded and presented in table and figure form. The data were analyzed using SPSS software version 25 with significant differences at 5%. The results of the study showed all treatments (p<0.05) in the expression of caspase 3 and caspase 10 in rat muscle. At dose of 150 mg/Kg BW can reduce the expression of caspase 3 and caspase 10 in rat muscle. Induction of Gagatan Harimau leaf nanoherbal as an antioxidant in male rats given swimming physical exercise showed improvements in muscle histology and morphology. A dose of 150 mg/Kg BW of nanoherbal Gagatan Harimau leaves was the best dose because it showed cell regeneration close to the normal treatment group.